HISTOLOGICAL CHARACTERISTIC OF THE CEREBELLUM IN THE CLIMBING PERCH (Anabas testudineus) - Sari, Yuslikha Khaniif Anggita; Ariana, Ariana; Widayanti, Rini; Pangestiningsih, Tri Wahyu (Jurnal Kedokteran Hewan, 2025)
Anatomical variations in brain shape and size among fish can be influenced by both species and habitat. The cerebellum of the fish brain, plays an essential role in balance regulation and the coordination of motor activity. However, information regarding the fundamental structure of the cerebellum in the climbing perch (Anabas testudineus) is still limited compared with zebrafish (Danio rerio) as the animal model. This study aimed to investigate the histological features of the climbing perch cerebellum. Transverse and sagitttal sections of the cerebellum were fixed in 10% neutral buffered formalin (NBF), processed into histological slides, and stained using cresyl violet. The parts of cerebellum and neurons morphology were observed using a light microscope equipped with Optilab then the resulting data were analyzed descriptively. The findings revealed that the cerebellum comprises three main parts: the corpus cerebelli, valvula cerebelli, and the vestibulolateral lobe, which includes the eminentia granularis and caudal lobe. The cerebellar cortex of the corpus and a valvula cerebelli consists of the molecular layer, ganglionic layer, and granular layer, while the vestibulolateral lobe is made up of a granular layer. Various neuronal types were identified, including rounded stellate cells, pear-shaped Purkinje cells, spindle-shaped eurydendroid cells, small rounded granular cells, and rounded or polygonal Golgi cells. In conclusion, while the cerebellar histology of Anabas testudineus is largely comparable to that of Danio rerio, its valvula cerebelli lacks the medial and lateral subdivisions found in the zebrafish.